Reducing Your Risk for Type 2 Diabetes: The Power of Food - Elena Torna; Jodi D. Fitzgerald; Danielle Nelson; Madison Woodard; Jeanette Andrade (EDIS, 2020)
Type 2 diabetes is a medical condition where you have too much sugar in your blood. According to the Centers for Disease Control, nearly 1 in 10 adults have Type 2 diabetes and 1 in 3 adults have pre-diabetes. This new 14-page publication of the UF/IFAS Food Science and Human Nutrition Department describes the modifiable risk factors for type 2 diabetes and tips to reduce your risk for diabetes. It also includes several example recipes. Written by Elena Torna, Jodi Fitzgerald, Danielle Nelson, Madison Woodard, and Jeanette Andrade. https://edis.ifas.ufl.edu/fs397